Are Black and Latino adolescents being asked if they use electronic cigarettes and advised not to use them? Results from a community-based survey - Connolly, Margaret; Croft, Daniel; Ramírez-Palacios, Paula; Cai, Xueya; Hill, Beverly; Orfin, Rafael H.; Rivera, M. Patricia; Wilson, Karen M.; Li, Dongmei; McIntosh, Scott; Ossip, Deborah J.; Cupertino, Ana Paula; et al. (Frontiers in Public Health, 2023)
Objective This study aimed to explore whether African American/Black and Hispanic/Latino adolescents are being asked about electronic cigarette (e-cigarette) use (vaping) and advised not to use them. Methods In 2021, adolescents (N = 362) with no vaping history, self-identified as African American/Black and/or Hispanic/Latino, and able to read and speak English and/or Spanish were recruited through partner schools and community-based organizations. Participants completed a survey reporting sociodemographic characteristics (e.g., race/ethnicity, gender, and language of preference) and they were asked about e-cigarette use and/or were advised not to use them by a health professional. Results In total, 12% of African American/Black and 5% of Hispanic/Latino participants reported not seeing a health professional in the year prior to enrollment. Of the participants who reported visiting a health professional, 50.8% reported being asked and advised about vaping. Over one-quarter (28.4%) of participants were neither asked nor advised regarding vaping. Compared to English-speaking participants, Spanish-speaking participants were significantly less likely to be asked about e-cigarette use (45.2 vs. 63.9%, p = 0.009) and advised not to use them (40.3 vs. 66.9%, p < 0.001). Moreover, compared to African American/Black participants, Hispanic/Latino participants were significantly less likely to be advised not to use e-cigarettes (52.9 vs. 68.6%, p = 0.018). Furthermore, compared to male participants, female participants were significantly less likely to be advised not to use e-cigarettes (51.3 vs. 68.2%, p = 0.003). Conclusion Compared to English-speaking participants, Spanish-speaking participants were significantly less likely to self-report being asked about e-cigarette use and advised not to use them. Moreover, Hispanic/Latino and female adolescents were significantly less likely to self-report being advised not to use e-cigarettes compared to their Black/African American and male counterparts. Future research is needed to improve health professional attention toward asking about and advising against vaping among adolescents.